2012
DOI: 10.7326/0003-4819-157-1-201206190-00429
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusion: A Clinical Practice Guideline From the AABB*

Abstract: These guidelines are based on a systematic review of randomized clinical trials evaluating transfusion thresholds. We performed a literature search from 1950 to February 2011 with no language restrictions. We examined the proportion of patients who received any RBC transfusion and the number of RBC units transfused to describe the effect of restrictive transfusion strategies on RBC use. To determine the clinical consequences of restrictive transfusion strategies, we examined overall mortality, nonfatal myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
663
2
16

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 957 publications
(711 citation statements)
references
References 49 publications
13
663
2
16
Order By: Relevance
“…RBC transfusion is a palliative therapeutic modality, and not a definitive treatment. Careful prior evaluation to determine the possible improvement in clinical symptoms by transfusion should be carried out before RBC transfusion [207]. RBC transfusion should be performed only when the advantages are considered to exceed the disadvantages, and the blood volume for transfusion should be as low as possible [32].…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…RBC transfusion is a palliative therapeutic modality, and not a definitive treatment. Careful prior evaluation to determine the possible improvement in clinical symptoms by transfusion should be carried out before RBC transfusion [207]. RBC transfusion should be performed only when the advantages are considered to exceed the disadvantages, and the blood volume for transfusion should be as low as possible [32].…”
Section: Rationalementioning
confidence: 99%
“…Therefore, the timing of the treatment of anemia by RBC transfusion should be determined considering the target Hb level. The condition of each patient should be carefully observed, and the blood volume for transfusion should be as low as possible [21,[207][208][209][210]. Before RBC transfusion, written informed consent should be obtained by practitioners after explaining the necessity and risks of RBC transfusion to the patient in an easy-tounderstand manner.…”
Section: Rationalementioning
confidence: 99%
“…2,10,11 In contrast, randomised controlled trials (RCTs) comparing a restrictive red blood cell transfusion threshold (allowing a participant's haemoglobin level to drop to a lower level before transfusing) with a more liberal strategy (transfusing a participant at a higher haemoglobin level) have not demonstrated adverse effects directly attributable to transfusion in patients undergoing major surgery or in the critically ill. [12][13][14] The absence of harm from restrictive practice in RCTs combined with the evidence from observational studies has been interpreted as being supportive of restrictive transfusion practice. 15 Alongside the well-documented risks of more liberal transfusion (including haemolytic and non-haemolytic transfusion reactions and transfusion-associated lung injury, 16 increasing demands on blood services 17 as well as additional and important cost implications associated with the storage, handling and administration of red blood cell units 18 ), this evidence has led to an emphasis on restrictive transfusion in contemporary blood management guidelines [19][20][21] and increasingly in health policy. 22,23 The Transfusion Indication Threshold Reduction (TITRe2) trial was designed in 2006 and was prompted by the widely varying transfusion thresholds that were being applied at the time and by a detailed observational analysis of data from the hospital in which the triallists worked.…”
Section: Background and Rationalementioning
confidence: 99%
“…The findings of this audit have led to the conclusion and recommendation that all centres should have a policy for blood management that should include the following: • A guideline 'trigger' Hb value of 8.0 g/dL is recommended because studies have shown that a restrictive transfusion policy is safe in otherwise stable isovolaemic patients, and guidelines [14,15] have endorsed this.This is a guideline, however, and must be used together with clinical evaluation.…”
Section: Resultsmentioning
confidence: 99%